Effect Of Antiseptic on Male Mice (Mus musculus L.) Body Weight - Hanizar, Evi; Rozza, Monica Ardilla; Maharani, Lila (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
The safety of using liquid soap to wash fruit or vegetables is unclear. The purpose of this study was to determine the effect of liquid soap on the body weight of mice (Mus musculus). This research is pure experimental using a completely randomized design. The treatment given was soaking fruits and vegetables in liquid soap with a concentration of 20 mL/L for 30 and 60 seconds, each treatment had 10 replications. The mice used were male, aged 4 weeks, with a total of 30 mice selected by cluster random sampling. Fruit and vegetable extracts were administered once daily, alternating fruit and vegetable extracts for 8 weeks in addition to the main food. Mice’s body weight was measured using a digital scale. The data were analyzed using One Way Anova and Duncan's advanced test. The results showed that liquid soap had a significant effect on the body weight of mice, but the average body weight of fruits and vegetables soaked in liquid soap for 30 seconds and 60 seconds was not significantly different. The conclusion of this study supports other research that the use of liquid soap containing surfactants for a long time continuously has a negative effect on body weight.